2020
DOI: 10.3390/cells9051205
|View full text |Cite
|
Sign up to set email alerts
|

UBQLN2 Promotes the Production of Type I Interferon via the TBK1-IRF3 Pathway

Abstract: Mutations of Ubiquilin 2 (UBQLN2) or TANK-binding kinase 1 (TBK1) are associated with amyotrophic lateral sclerosis and frontotemporal degeneration (ALS/FTD). However, the mechanisms whereby UBQLN2 or TBK1 mutations lead to ALS and FTD remain unclear. Here, we explored the effect of UBQLN2 on TBK1 in HEK-293T cells or in CRISPR–Cas9-mediated IRF3 and IRF7 knockout (KO) cells. We found an interaction between TBK1 and UBQLN2, which was affected by ALS/FTD-linked mutations in TBK1 or UBQLN2. Co-expression of UBQL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
(97 reference statements)
1
7
0
Order By: Relevance
“…All rats were maintained on Sprague-Dawley background. As characterized previously [ 6 ], CaMKα2-tTA transgenic rats [ 31 ] were crossed with TRE-UBQLN2 P497H transgenic rats to generate bigenic rats. Breeding rats were fed doxycycline (DOX) (50 μg/mL) (Sigma, St Louis, MI, USA) in drinking water during embryonic development.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All rats were maintained on Sprague-Dawley background. As characterized previously [ 6 ], CaMKα2-tTA transgenic rats [ 31 ] were crossed with TRE-UBQLN2 P497H transgenic rats to generate bigenic rats. Breeding rats were fed doxycycline (DOX) (50 μg/mL) (Sigma, St Louis, MI, USA) in drinking water during embryonic development.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmids were constructed as previously described [ 31 ], and a 3× FLAG tag was fused to the C-terminal of human UBQLN2. HEK-293T cells were obtained from American Type Culture Collection (ATCC, Manassas, VA, USA) and were cultured in Dulbecco’s modified Eagle medium supplemented with 10% fetal bovine serum (FBS) and antibiotics (ampicillin and streptomycin).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies had shown that upregulation of UBQLN2 regulates Nuclear Factor kappa-B signaling in inflammation and pathogenicity [175]. More recently Chen et al found UBQLN2 binds directly with TBK1, promoting phosphorylation and activation of the kinase and interferon signaling [174].…”
Section: Accepted Articlementioning
confidence: 98%
“… Signaling molecule Classification Regulator Function Ref. TBK1 PTMs Positive MIB K63-linked ubiquitination 161 TBK1 K63-linked ubiquitination 154 Nrdp1 K63-linked ubiquitination 163 RNF128 K63-linked ubiquitination 162 USP1–UAF1 complex Deubiquitination 164 UBQLN2 Phosphorylation 159 Src Autophosphorylation 160 TBK1 Autophosphorylation 155 RKIP Autophosphorylation 158 GSK3β Self-association and autophosphorylation 157 Dnmt3a Recruitment of HDAC9 for deacetylation 165 HDAC3 Deacetylation 166 TRIM9 Recruitment of GSK3β for activation 157 Negative ASB8 K48-linked ubiquitination 172 USP38 K48-linked ubiquitination 176 DYRK2 K48-linked ubiquitination 174 THOC7 K48-linked ubiquitination 175 TRIP K48-linked ubiquitination 173 Siglec1 Recru...…”
Section: Role Of Ptms In Regulating Signal Transductionmentioning
confidence: 99%
“…TRIM9 short isoform (TRIM9s) facilitates the recruitment of GSK3β to TBK1 upon viral infection 157 , and Raf kinase inhibitory protein serves as a positive regulator 158 ; both of these proteins promote autophosphorylation of TBK1. Moreover, ubiquilin 2 (UBQLN2) promotes the stability and facilitates the phosphorylation of TBK1 159 , and Tyr179 (Y179) phosphorylation (catalyzed by the tyrosine kinase Src) is essential for the initiation of TBK1 autophosphorylation 160 . Ubiquitination also plays a critical role in the activation of TBK1.…”
Section: Regulation Of Tbk1 By Host Factorsmentioning
confidence: 99%